Renouncing the world yet leading the church : the monk-bishop in late antiquity - Sterk, Andrea (Harvard University Press, 2004)
In the 4th-6th centuries, the monk-bishop became the dominant model of ecclesiastical leadership in the eastern Roman Empire and Byzantium. Andrea Sterk explores the social, political intellectual and theological grounding for this development.